Multi-Image Pinhole Viewer Using a Biscuit. (January 2018) - Cabe, Patrick A.
A camera obscura-type viewer based on pinhole optics, with the apertures being the holes in a commercial snack biscuit (or cracker), produces interesting and easily obtainable projected images, as demonstrated during the 2017 solar eclipse.